The Role of Striatal-Enriched Protein Tyrosine Phosphatase (STEP) in Cognition - Fitzpatrick, Christopher J.; Lombroso, Paul J. (Frontiers in Neuroanatomy, 2011)
STriatal-Enriched protein tyrosine Phosphatase (STEP) has recently been implicated in several neuropsychiatric disorders with significant cognitive impairments, including Alzheimer’s disease, schizophrenia, and fragile X syndrome. A model has emerged by which STEP normally opposes the development of synaptic strengthening and that disruption in STEP activity leads to aberrant synaptic function. We review the mechanisms by which STEP contributes to the etiology of these and other neuropsychiatric disorders. These findings suggest that disruptions in STEP activity may be a common mechanism for cognitive impairments in diverse illnesses.